INFEKSI JAMUR CANDIDA PADA PENDERITA HIV/AIDS - Lestari, Pujiana Endah (Fakultas Kedokteran Gigi Universitas Jember, 2013)
HIV / AIDS remains a global problem, more than 34 million people infected with HIV / AIDS. When a person with HIV / AIDS will become vulnerable to opportunistic infections. Manifestations of Candida fungal opportunistic infections in people with HIV / AIDS is most commonly a Oropharyngeal candidiasis. In addition, oral fungal infections include: acute pseudomembranous candidiasis, acute atrophic candidiasis, chronic atrophic candidiasis, chronic hyperplastic candidiasis and candida cheilosis. Fungal infections are common in people with HIV / AIDS as it relates to the level of immunosuppression, which can be an indicator of HIV infection and prediction of progression to AIDS infection.